MOTIVATION FOR LEARNING AND ENGLISH CONVERSATION THROUGH FILM MEDIA WITH DUBBED AND SUBTITLED METHODS - Musdalifah Musdalifah; Satriani Satriani (Jurnal Abdimas Indonesia, 2021)
The key to inspiring pupils to study and communicate in English is to provide engaging educational media and effective learning methods. One of the most intriguing is the use of cinema media as a teaching medium. The film tells an intriguing story in the style of graphic animation and includes auditory sound to captivate students who want to learn English. Furthermore, effective learning strategies can help students understand what they are being taught. One of the learning approaches that can be utilized to urge students to communicate in English is to use dubbing and subtitling. Dubbing is a technique for imitating the voices of actors in films who perform certain parts. Because they appear to be acting out film dialogue scenes depicted by actors, this helps increase pupils' interest in conversing in English. The method of showing film dialogue at the bottom of the screen is known as subtitles. In other words, as a tool for students to absorb the material supplied, teaching media and learning methods are linked and mutually beneficial. Students can be helped to engage in language learning while also being motivated to speak in English using effective and efficient media and approaches.